Respuesta :

Answer:

[tex](3,-4)[/tex]

Step-by-step explanation:

Given

[tex]-7x - 2y = -13[/tex]

[tex]x = 2y + 11[/tex]

Required

Find the solution

Substitute [tex]2y + 11[/tex] for x in the first equation

[tex]-7(2y + 11) - 2y = -13[/tex]

Open bracket

[tex]-14y -77 - 2y = -13[/tex]

Collect Like Terms

[tex]-14y - 2y = -13+77[/tex]

[tex]-16y = 64[/tex]

Solve for y

[tex]y = \frac{64}{-16}[/tex]

[tex]y = -4[/tex]

Substitute -4 for y in [tex]x = 2y + 11[/tex]

[tex]x = 2(-4) + 11[/tex]

[tex]x = -8 +11[/tex]

[tex]x = 3[/tex]

Hence, the solution is [tex](3,-4)[/tex]